Efficient Zigzag Theory for Static and Free Vibration Response of Rectangular FGM Panels - Das, T.; K Nath, J. (International Journal of Engineering and Technology, 2018)
An efficient zigzag theory is presented for static and free vibration response of rectangular panels whose layers are made up of a number of functionally graded materials. In order to create a suitable FGM panel laminate, an analytical formulation is developed using an efficient zigzag theory. Different FGM layers have been stacked one over another and perfect interlaminar bonding is assumed between them. As far as manufacturing of such FGM panel is concerned, the technique of 3D printing can be utilized to create it through a single continuous operation. The resulting analytical model is used to identify critical locations and parameters that are responsible for material failure as well as material property variation across panel thickness to enhance productivity and quality of the designed panel. The technique will significantly reduce the time and computational cost involved with analysis of FGM materials and will provide a basis for finite element implementation.Â Â